1982
DOI: 10.1161/01.hyp.4.5.581
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a vascular sensitizing factor in plasma of saline-loaded dogs.

Abstract: SUMMARY This study investigates whether plasma extracts previously demonstrated to have natriuretic and antinatriferic activity have effects on vascular reactivity of rat cremaster arterioles. Plasma from hydropenic and saline-loaded dogs was subjected to Diafiltration, and eluted on a strong cation exchange column (SCX). The effects of intraarterial injections of various column fractions on constrictor responses to repeated injections of 33.3 ng of norepinephrine (NE) were used to indicate changes in vascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

1983
1983
1991
1991

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…The relation between volume expansion and arteriolar reactivity has not been established; however, there may be a link between the elevated blood volume and the release of a natriuretic compound that could alter vascular tone or mechanics, or both, and thus, alter reactivity to pressure. 38 Therefore, the increased blood volume in renal hypertension may have resulted in arteriolar autoregulation and vasoconstriction through a change in the mechanical properties or the sensitivity of the vascular smooth muscle to vasoactive stimuli.…”
Section: Autoregulation In Hypertensionmentioning
confidence: 99%
“…The relation between volume expansion and arteriolar reactivity has not been established; however, there may be a link between the elevated blood volume and the release of a natriuretic compound that could alter vascular tone or mechanics, or both, and thus, alter reactivity to pressure. 38 Therefore, the increased blood volume in renal hypertension may have resulted in arteriolar autoregulation and vasoconstriction through a change in the mechanical properties or the sensitivity of the vascular smooth muscle to vasoactive stimuli.…”
Section: Autoregulation In Hypertensionmentioning
confidence: 99%
“…A canine plasma extract that inhibits Na+,K+ ATPase released by volume expansion has been observed to have digoxin-like immuno reactivity (3), and the endogenous digitalis like substance increases sensitivity to the vaso constrictive effects of norepinephrine and angiotensin (4). Hamlyn et al (5) showed that the Na+,K±ATPase inhibitory activity of a plasma substance was related to the high blood pressure in subjects with essential hypertension and suggested the involvement of a circulating Na+ pump inhibitor in the gen esis of essential hypertension.…”
mentioning
confidence: 99%
“…Digoxin-like immunoreactive sub stances in unpurified material are not neces sarily always the same as the substances with Na+,K+-ATPase inhibitory activity (14), but only one of the studies determined the Na+,K+-ATPase inhibitory activities of the substances (8). Unfortunately, even when the enzyme activity was assayed (4,8), the assay mixtures employed contained a high K+ con centration; under such a condition, the observed inhibitory activity would include the non-specific (i.e., non ouabain-like) inhibitory activity (15).…”
mentioning
confidence: 99%
“…It has been assumed that EDLF has a vasoconstrictor property (Plunkett et al 1982;Soldin 1986). However, no report is available as to vasoconstrictor action of the natriuretic fraction in isolated vascular muscle preparation.…”
mentioning
confidence: 99%